DAMPAK KUALITAS PELAYANAN, RESPONSIVITAS, DAN KECEPATAN LAYANAN TERHADAP KEPUASAN MASYARAKAT DALAM PEMENUHAN KEBUTUHAN DARAH PADA PMI KABUPATEN BIREUEN - ACEH - Edi Saputra; Chairul Bariah; Zalikha Zalikha; Murni Murni (IndOmera, 2026)
The need for blood in the community continues to increase, so the Indonesian Red Cross (PMI), which serves as a blood provider, actively works from time to time. Public satisfaction in meeting blood needs requires the PMI to improve service quality, responsiveness to requests, and speed of service. This study aims to analyze factors related to public satisfaction served by the PMI Bireuen Regency Branch. The study was conducted using a satisfaction survey of 97 people in need of blood at the PMI Bireuen Regency Branch using purposive sampling. The study employed a quantitative associative research method and data analysis using a structural (path) model. The results revealed that: (1) service quality, responsiveness, and speed of service are causally related and have both direct and indirect impacts on public satisfaction. Service quality was 58.6%, responsiveness was 56.02%, and speed of service was 65.77%. (2) Simultaneously, service quality, responsiveness, and speed of service contributed significantly and positively to public satisfaction in meeting blood needs, amounting to 65.3%.